Oral immunotherapy for milk allergy - Yeung, Joanne P; Kloda, Lorie A; McDevitt, Jason; Ben-Shoshan, Moshe; Alizadehfar, Reza (Cochrane database of systematic reviews, 2012)
The mainstay of treatment of IgE-mediated cow milk allergy (IMCMA) is an avoidance diet, which is especially difficult with a ubiquitous food like milk. Milk oral immunotherapy (MOIT) may be an alternative treatment, through desensitization or induction of tolerance. We aim to assess the clinical efficacy and safety of MOIT in children and adults with IMCMA as compared to a placebo treatment or avoidance strategy. We searched 13 databases for journal articles, conference proceedings, theses and unpublished trials, without language or date restrictions, using a combination of subject headings and text words. The search is up-to-date as of October 1, 2012. Only randomised controlled trials (RCT) were considered for inclusion. Blinded and open trial designs were included. Children and adults with IMCMA were included. MOIT administered by any protocol were included. A total of 2111 unique records were identified and screened for potential inclusion. Studies were selected, data extracted and methodological quality assessed independently by two reviewers. We attempted to contact the study investigators to inquire about data not published that was required for the analysis. Statistical heterogeneity was assessed using the I² test. We estimated a pooled risk ratio (RR) for each outcome using a Mantel-Haenzel fixed-effect model if statistical heterogeneity was low as evaluated by an I² value less than 50%. Of 157 records reviewed, 16 were included, representing five trials. In general, the studies were small and had inconsistent methodological rigor. Overall, the quality of evidence was rated as low. Each study used a different MOIT protocol. A total of 196 patients were studied (106 MOIT, 90 control) and all were children. Three studies were blinded and two used an avoidance diet control.  Sixty-six patients (62%) in the MOIT group were able to tolerate a full serving of milk (about 200 mL) compared to seven (8%) of the control group (RR 6.61, 95% CI 3.51 to 12.44). In addition, 27 (25%) in the MOIT group could ingest a partial serving of milk (10 to 184 mL) while none could in the control group (RR 9.34, 95% CI 2.72 to 32.09). None of the studies assessed the patients following a period off immunotherapy. Adverse reactions were common (97 of 106 MOIT patients had at least one symptom), although most were local and mild. Because of variability in reporting methods, adverse effects could not be combined quantitatively. For every 11 patients receiving MOIT, one required intramuscular epinephrine. One patient required it on two occasions. Studies to date have involved small numbers of patients and the quality of evidence is generally low. The current evidence shows that MOIT can lead to desensitization in the majority of individuals with IMCMA although the development of long-term tolerance has not been established. A major drawback of MOIT is the frequency of adverse effects, although most are mild and self-limited. The use of parenteral epinephrine is not infrequent. Because there are no standardized protocols, guidelines would be required prior to incorporating desensitization into clinical practice.